2017
DOI: 10.1002/jhbp.461
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of liver resection with continued antiplatelet therapy using aspirin

Abstract: Liver resection can be safely performed while continuing aspirin therapy without increasing hemorrhagic morbidity. Our results suggest that interruption of aspirin therapy is unnecessary for patients undergoing liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The risk of developing hemorrhagic complications during or after surgery in patients with ATT remains uncertain. While several studies have reported the increasing risk of perioperative hemorrhagic complications with ATT [1][2][3], the safety and feasibility of surgery for patients with continuous aspirin therapy have also been reported recently in two randomized clinical trials regarding non-cardiac surgery [4,5] and several retrospective studies regarding abdominal surgery [6][7][8]. Chassot et al [9] recommend continuing aspirin preoperatively when prescribed as secondary prevention or cardiovascular disease or stroke because the risk of cardiovascular events when withdrawing them is generally higher than the risk of surgical bleeding.…”
Section: Introductionmentioning
confidence: 98%
“…The risk of developing hemorrhagic complications during or after surgery in patients with ATT remains uncertain. While several studies have reported the increasing risk of perioperative hemorrhagic complications with ATT [1][2][3], the safety and feasibility of surgery for patients with continuous aspirin therapy have also been reported recently in two randomized clinical trials regarding non-cardiac surgery [4,5] and several retrospective studies regarding abdominal surgery [6][7][8]. Chassot et al [9] recommend continuing aspirin preoperatively when prescribed as secondary prevention or cardiovascular disease or stroke because the risk of cardiovascular events when withdrawing them is generally higher than the risk of surgical bleeding.…”
Section: Introductionmentioning
confidence: 98%
“…To prevent ischemic or thromboembolic events in patients with the indication of AP therapy, the application of antiplatelet therapies is rapidly increasing, especially considering the aging of population [11][12][13]. Therefore, a clinical dispute arises that whether patients with both primary ICH and the indication of AP therapy should resume AP therapy [14].…”
Section: Introductionmentioning
confidence: 99%
“…Because of the risk of ICH recurrence, primary ICH is usually considered as contraindication of AP therapy [14]. However, without AP therapy, many patients may suffer from ischemic and thromboembolic events.…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, using PSM analysis to alleviate statistical bias, the safety of preoperative aspirin continuation during liver resection was also demonstrated. The recent study conducted by Monden et al 19 showed that bleeding-related complication did not increase during or after liver resection in patients receiving continued aspirin. However, the number of cases in their study was small, and there were significant differences in patients' background.…”
Section: Discussionmentioning
confidence: 93%